2019
DOI: 10.1002/est2.37
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamic evaluation of heat transfer enhancement in microchannel solar collectors sustained by alumina nanofluid

Abstract: Nanofluids have produced a wide range of researches for various cooling/heating purposes, owing to the enhanced thermophysical properties they bring by suspending nanoparticles in the base fluid. This work proposes a detailed computational fluid dynamic (CFD) study of heat transfer enhancement in microchannel solar collectors coupled with nanofluid. The accuracy of the numerical model is ensured through a reliable finite element analysis considering the complexity of the three‐dimensional structure of microcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…In figures 4(b) and 5, the temperature of the fluid at the end of the channel is higher than the temperature of the solar cell at that moment. In the same way, as Ahadi et al demonstrated, the accumulation of energy leads locally to a significant increase in the temperature being maximum [35].…”
Section: Model 2: Serpentine Structure Channelmentioning
confidence: 53%
“…In figures 4(b) and 5, the temperature of the fluid at the end of the channel is higher than the temperature of the solar cell at that moment. In the same way, as Ahadi et al demonstrated, the accumulation of energy leads locally to a significant increase in the temperature being maximum [35].…”
Section: Model 2: Serpentine Structure Channelmentioning
confidence: 53%